1987
DOI: 10.1111/j.1439-0418.1987.tb00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Fliegen der Gattung Platypalpus (Diptera, Empididae) — bisher wenig beachtete Prädatoren im Getreidebestand

Abstract: Flies of Genus Platypalpus in cereal crops as predatory insects little noticed hitherto Sweep net and blue‐trap catches carried out in cereal crops of the Halle district in 1985 proved the presence of predatory flies of the genus Platypalpus (Empididae) in great number. The identification of altogether 6506 insects caught in winter wheat, winter and summer barley revealed 12 different species. Most frequently were found Platypalpus articulatoides Frey, P. pallidicornis Coll., P. articulatus Macq. and P. pictit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Among them, there are pests like the wheat midge Contarinia tritici, which has been recorded as prey of Platypalpus pallidiventris (Barnes, 1932). Another possible prey is the frit fly Oscinella frit (Jones, 1965;Stark & Wetzel, 1987). Smaller species of the genus Platypalpus were also recorded to feed on Thysanoptera (Stark, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, there are pests like the wheat midge Contarinia tritici, which has been recorded as prey of Platypalpus pallidiventris (Barnes, 1932). Another possible prey is the frit fly Oscinella frit (Jones, 1965;Stark & Wetzel, 1987). Smaller species of the genus Platypalpus were also recorded to feed on Thysanoptera (Stark, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…They have a small range of activity compared to other antagonists, and their populations are extremely susceptible to any disturbances. As a study model, predatory flies of the genus Platypalpus may be suitable, because they are important natural antagonists of crop-damaging flies and midges [228][229][230]. Because the larvae of predatory flies develop in the soil [229], active soil life is conducive to the abundance and diversity of species of these natural antagonists.…”
Section: Impact On Natural Regulatory Processesmentioning
confidence: 99%
“…The ecological value of this group has been unclear for a long time. However, a number of investigations have shown that adult Platypalpus are important regulators (as very active predators) of the population density of many phytophagous Diptera, including some important pests (Chva ´la 1975;Stark and Wetzel 1987).…”
mentioning
confidence: 99%